Mental fatigue in football: Is it time to shift the goalposts? An evaluation of the current methodology - Thompson, C. J.; Fransen, J.; Skorski, S.; Smith, M. R.; Meyer, T.; Barrett, S.; Coutts, A. J. (Sports Medicine, 2019)
Research in football for a long time has focused on the physical nature of fatigue as opposed to its mental aspects. However, since 2016, six original articles have investigated the effects of induced mental fatigue in football on isolated physical, skill and decision-making performance tests, along with physical, technical and tactical performance outcomes in small-sided games. Whilst these studies have overall shown a negative impact of mental fatigue on task performance, this current opinion aims to critically examine the methodological approach to this problem, most notably the lack of ecological validity when inducing mental fatigue and the present approach to measuring mental fatigue using visual analogue scales (VAS). It is suggested that future research on mental fatigue in football may benefit from the use of surveys/interviews to understand the true cognitive demands of elite football players. Additionally, future research should aim to reduce the reliance on using VAS to measure mental fatigue as results from this tool may be confounded by several response biases. In conclusion, this article highlights the need for mentally fatiguing tasks that adequately represent football-associated mental fatigue and assessments of mental fatigue that minimise the confounding effect of response bias.